2008
DOI: 10.1213/ane.0b013e318186641d
|View full text |Cite
|
Sign up to set email alerts
|

Low Volume and High Concentration of Local Anesthetic Is More Efficacious than High Volume and Low Concentration in Labat's Sciatic Nerve Block: A Prospective, Randomized Comparison

Abstract: In Labat's sciatic nerve blockade, administering a low volume and a high concentration of local anesthetic (1.5% mepivacaine) is associated with a higher success rate and a shorter onset time than a high volume and a low concentration of solution (1% mepivacaine).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 23 publications
1
28
0
1
Order By: Relevance
“…8 For transgluteal sciatic nerve blocks, Taboada Muñiz et al 8 observed that, compared with mepivacaine 1% (30 mL), mepivacaine 1.5% (20 mL) resulted in a higher success rate as well as a shorter onset time for sensory and motor block. Similarly, Smith and Siggins 7 found that, compared with prilocaine 1% (0.25 mL/kg), prilocaine 3% (0.08 mg/kg) provided a quicker sensory and motor block.…”
Section: Discussionmentioning
confidence: 99%
“…8 For transgluteal sciatic nerve blocks, Taboada Muñiz et al 8 observed that, compared with mepivacaine 1% (30 mL), mepivacaine 1.5% (20 mL) resulted in a higher success rate as well as a shorter onset time for sensory and motor block. Similarly, Smith and Siggins 7 found that, compared with prilocaine 1% (0.25 mL/kg), prilocaine 3% (0.08 mg/kg) provided a quicker sensory and motor block.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, PNB with a higher concentration of local anesthetic was associated with increased success rate, decreased postoperative pain scores, and prolonged duration of analgesia, compared to lower anesthetic concentration of the same volume 11. In addition, PNB with lower volume and higher concentration of local anesthetic was more efficacious than higher volumes and lower concentrations of local anesthetic of equivalent dose 12,13…”
Section: Introductionmentioning
confidence: 90%
“…24Y26,29,30,34,36Y38,41,42 Partial or complete sensory and motor block comprised a component of block success in 5 trials. 32,33,39,40,43 Five trials either wholly or partially defined block success as no conversion to GA. 28,32,35,43,44 Table 2 presents the various definitions of block success used by the source trials reviewed.…”
Section: Definition Of Block Successmentioning
confidence: 99%